Analysis of coating performances in machining titanium alloys for aerospace applications. (1st January 2013) - Nouari, M.; Calamaz, Madalina; Haddag, B.; Girot, Franck
The current study emphasises the role of coating materials in enhancing the wear resistance of the cutting tool and improving the tool-chip contact. The wear mechanisms have been investigated through a series of cutting experiments performed on an instrumented planer machine. Machining tests were conducted on the usual Ti-6Al-4V alloy (workpiece) and cemented carbide tools. Four new coatings were especially designed for the study: 1 diamond (thin layer, about 2 to 3 μm) 2 diamond+TiB2+CrN/DLC (diamond like carbon, about 3, 5 μm) 3 diamond (thick layer, 6 μm) 4 TiB2+CrN/DLC (3 μm). The performance of each coating material was analysed and compared in one hand to the uncoated carbide tools and on the other hand to the CBN reinforced carbide tools in terms of cutting forces and tool wear mechanisms.